Besleria mucosa: a new species of Gesneriaceae with mucilage from the Serranía de los Paraguas, Cordillera Occidental, Colombia - Gabriel E. Ferreira; Alejandro Zuluaga; Michael J. G. Hopkins; Andréa O. Araujo; Mathieu Perret; Alain Chautems; Laura Clavijo (Brittonia, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Soil microbial community structure and carbon dynamics in response to compost and livestock management in grassland soils - Laura L. de Sosa; María José Carpio; Marta Gil-Martínez; Mathieu Thevenot; Olivier Mathieu; Engracia Madejón; Marco Panettieri (Agriculture, Ecosystems & Environment, 2026)

Sensitivity and Specificity of the Poststroke Spasticity Monitoring Questionnaire (PSMQ) for Remote Monitoring of Spasticity Development: Interim Analysis From an Ongoing Epidemiology Study - Richard D. Zorowitz; Laura Serrano Barrenechea; Simon Butet; David Hernández Herrero; Rama Prasad; Pascal Lecomte; Sophie Vandenbremt; Simon Page; Mathieu Beneteau; Pascal Maisonobe; Alessandro Picelli (Toxicon, 2026)

Life cycle assessment of four waste-to-energy plant configurations equipped with post-combustion carbon capture and storage - Laura Herraiz; Iain Struthers; Dan Su; Hasan Muslemani; Mathieu Lucquiaud; R. Camilla Thomson (International Journal of Greenhouse Gas Control, 2026)

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

Agroecological genomics and participatory science: optimizing crop mixtures for agricultural diversification - Chiara Santamarina; Laura Mathieu; Elena Bitocchi; Alice Pieri; Elisa Bellucci; Valerio Di Vittori; Karolina Susek; Federico Scossa; Laura Nanni; Roberto Papa (Trends in Plant Science, 2025)

Bridging dimensions: a comparative analysis of 2D and 3D in vitro models for hepatocellular carcinoma research - Leticia C. Valente; Luana Riechelman-Casarin; Laura L. P. Esteves; Gabriel P. Bacil; Tereza Cristina da Silva; Mathieu Vinken; Bruno Cogliati; Scott L. Friedman; Amedeo Columbano; Luís Fernando Barbisan; Guilherme R. Romualdo (Archives of Toxicology, 2025)

Recovery of tree species functional composition in eucalypt plantations with natural regeneration differs among canopy strata - Laura H.P. Simões; Marielos Peña-Claros; Joannès Guillemot; Rens Brouwer; Frans Bongers; Lourens Poorter; Catherine T. de Almeida; Danilo R.A. Almeida; Miguel Cooper; Mathieu Decuyper; José G. Fernandes Neto; Matheus S. Fuza; et al. (Forest Ecology and Management, 2025)

Functional recovery of tropical forests: The role of restoration methods and environmental conditions - Rens Brouwer; Marielos Peña-Claros; Frans Bongers; Lourens Poorter; Joannès Guillemot; Danilo R.A. Almeida; Catherine Torres de Almeida; Angélica F. Resende; Laura H.P. Simões; Natália M. Ivanauskas; Renato A. Ferreira de Lima; Vinicius Castro Souza; et al. (Biological Conservation, 2025)

Towards an assessment of psychosocial work factors in a multi-level mental health intervention in the workplace: results from the MENTUPP pilot-study - Fotini Tsantila; Reiner Rugulies; Evelien Coppens; Hans De Witte; Ella Arensman; Abdulla Kahar; Arlinda Cerga-Pashoja; Paul Corcoran; Lars De Winter; Birgit Greiner; Eve Griffin; Bridget Hogg; et al. (International Archives of Occupational and Environmental Health, 2024)

Behavioral Treatment for Speech and Language in Primary Progressive Aphasia and Primary Progressive Apraxia of Speech: A Systematic Review - Lisa D. Wauters; Karen Croot; Heather R. Dial; Joseph R. Duffy; Stephanie M. Grasso; Esther Kim; Kristin Schaffer Mendez; Kirrie J. Ballard; Heather M. Clark; Leeah Kohley; Laura L. Murray; Emily J. Rogalski; et al. (Neuropsychology Review, 2024)
Primary progressive aphasia (PPA) and primary progressive apraxia of speech (PPAOS) are neurodegenerative syndromes characterized by progressive decline in language or speech. There is a growing number of studies investigating speech-language interventions for PPA/PPAOS. An updated systematic evaluation of the treatment evidence is warranted to inform best clinical practice and guide future treatment research. We systematically reviewed the evidence for behavioral treatment for speech and language in this population. Reviewed articles were published in peer-reviewed journals through 31 May 2021. We evaluated level of evidence, reporting quality, and risk of bias using a modified version of the American Speech-Language Hearing Association (ASHA) Levels of Evidence, an appraisal point system, additional reporting quality and internal/external validity items, and, as appropriate, the Single Case Experimental Design Scale or the Physiotherapy Evidence Database – PsycBITE Rating Scale for Randomized and Non-Randomized Controlled Trials . Results were synthesized using quantitative summaries and narrative review. A total of 103 studies reported treatment outcomes for 626 individuals with PPA; no studies used the diagnostic label PPAOS. Most studies evaluated interventions for word retrieval. The highest-quality evidence was provided by 45 experimental and quasi-experimental studies (16 controlled group studies, 29 single-subject designs). All ( k = 45/45) reported improvement on a primary outcome measure; most reported generalization ( k = 34/43), maintenance ( k = 34/39), or social validity ( k = 17/19) of treatment for at least one participant. The available evidence supports speech-language intervention for persons with PPA; however, treatment for PPAOS awaits systematic investigation. Implications and limitations of the evidence and the review are discussed.

The root of plant-plant interactions: Belowground special cocktails - Laura Mathieu; Elsa Ballini; Jean-Benoit Morel; Louis-Valentin Méteignier (Current Opinion in Plant Biology, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Effects of climate on the distribution and conservation of commonly observed European earthworms - Romy Zeiss; Maria J. I. Briones; Jérome Mathieu; Angela Lomba; Jessica Dahlke; Laura‐Fiona Heptner; Gabriel Salako; Nico Eisenhauer; Carlos A. Guerra (Conservation Biology, 2024)
Belowground biodiversity distribution does not necessarily reflect aboveground biodiversity patterns, but maps of soil biodiversity remain scarce because of limited data availability. Earthworms belong to the most thoroughly studied soil organisms and—in their role as ecosystem engineers—have a significant impact on ecosystem functioning. We used species distribution modeling (SDMs) and available data sets to map the spatial distribution of commonly observed (i.e., frequently recorded) earthworm species (Annelida, Oligochaeta) across Europe under current and future climate conditions. First, we predicted potential species distributions with commonly used models (i.e., MaxEnt and Biomod) and estimated total species richness (i.e., number of species in a 5 × 5 km grid cell). Second, we determined how much the different types of protected areas covered predicted earthworm richness and species ranges (i.e., distributions) by estimating the respective proportion of the range area. Earthworm species richness was high in central western Europe and low in northeastern Europe. This pattern was mainly associated with annual mean temperature and precipitation seasonality, but the importance of predictor variables to species occurrences varied among species. The geographical ranges of the majority of the earthworm species were predicted to shift to eastern Europe and partly decrease under future climate scenarios. Predicted current and future ranges were only poorly covered by protected areas, such as national parks. More than 80% of future earthworm ranges were on average not protected at all (mean [SD] = 82.6% [0.04]). Overall, our results emphasize the urgency of considering especially vulnerable earthworm species, as well as other soil organisms, in the design of nature conservation measures.

Plant-TFClass: a structural classification for plant transcription factors - Romain Blanc-Mathieu; Renaud Dumas; Laura Turchi; Jérémy Lucas; François Parcy (Trends in Plant Science, 2024)

Correction: Outcome assessment of a complex mental health intervention in the workplace. Results from the MENTUPP pilot study - Fotini Tsantila; Evelien Coppens; Hans De Witte; Ella Arensman; Benedikt Amann; Arlinda Cerga-Pashoja; Paul Corcoran; Johanna Creswell-Smith; Grace Cully; Monika Ditta Toth; Birgit Greiner; Eve Griffin; et al. (International Archives of Occupational and Environmental Health, 2023)

Effects of weathering on the properties and fate of secondary microplastics from a polystyrene single-use cup - Olubukola S. Alimi; Dominique Claveau-Mallet; Mathieu Lapointe; Thinh Biu; Lan Liu; Laura M. Hernandez; Stéphane Bayen; Nathalie Tufenkji (Journal of Hazardous Materials, 2023)

Outcome assessment of a complex mental health intervention in the workplace. Results from the MENTUPP pilot study - Fotini Tsantila; Evelien Coppens; Hans De Witte; Ella Arensman; Benedikt Amann; Arlinda Cerga-Pashoja; Paul Corcoran; Johanna Creswell-Smith; Grace Cully; Monika Ditta Toth; Birgit Greiner; Eve Griffin; et al. (International Archives of Occupational and Environmental Health, 2023)
Objective Multicomponent interventions are recommendable to achieve the greatest mental health benefits, but are difficult to evaluate due to their complexity. Defining long-term outcomes, arising from a Theory of Change (ToC) and testing them in a pilot phase, is a useful approach to plan a comprehensive and meaningful evaluation later on. This article reports on the pilot results of an outcome evaluation of a complex mental health intervention and examines whether appropriate evaluation measures and indicators have been selected ahead of a clustered randomised control trial (cRCT). Methods The MENTUPP pilot is an evidence-based intervention for Small and Medium Enterprises (SMEs) active in three work sectors and nine countries. Based on our ToC, we selected the MENTUPP long-term outcomes, which are reported in this article, are measured with seven validated scales assessing mental wellbeing, burnout, depression, anxiety, stigma towards depression and anxiety, absenteeism and presenteeism. The pilot MENTUPP intervention assessment took place at baseline and at 6 months follow-up. Results In total, 25 SMEs were recruited in the MENTUPP pilot and 346 participants completed the validated scales at baseline and 96 at follow-up. Three long-term outcomes significantly improved at follow-up ( p < 0.05): mental wellbeing, symptoms of anxiety, and personal stigmatising attitudes towards depression and anxiety. Conclusions The results of this outcome evaluation suggest that MENTUPP has the potential to strengthen employees’ wellbeing and decrease anxiety symptoms and stigmatising attitudes. Additionally, this study demonstrates the utility of conducting pilot workplace interventions to assess whether appropriate measures and indicators have been selected. Based on the results, the intervention and the evaluation strategy have been optimised.

On the cost of zero carbon hydrogen: A techno-economic analysis of steam methane reforming with carbon capture and storage - Daniel Mullen; Laura Herraiz; Jon Gibbins; Mathieu Lucquiaud (International Journal of Greenhouse Gas Control, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Consensus Recommendations for Clinical Outcome Assessments and Registry Development in Ataxias: Ataxia Global Initiative (AGI) Working Group Expert Guidance - Thomas Klockgether; Matthis Synofzik; Saud Alhusaini; Mathieu Anheim; Irina Antonijevic; Tee Ashizawa; Luis Bataller; Mélanie Berard; Enrico Bertini; Sylvia Boesch; Pedro Braga-Neto; Emanuel Cassou; et al. (The Cerebellum, 2023)
To accelerate and facilitate clinical trials, the Ataxia Global Initiative (AGI) was established as a worldwide research platform for trial readiness in ataxias. One of AGI’s major goals is the harmonization and standardization of outcome assessments. Clinical outcome assessments (COAs) that describe or reflect how a patient feels or functions are indispensable for clinical trials, but similarly important for observational studies and in routine patient care. The AGI working group on COAs has defined a set of data including a graded catalog of COAs that are recommended as a standard for future assessment and sharing of clinical data and joint clinical studies. Two datasets were defined: a mandatory dataset (minimal dataset) that can ideally be obtained during a routine clinical consultation and a more demanding extended dataset that is useful for research purposes. In the future, the currently most widely used clinician-reported outcome measure (ClinRO) in ataxia, the scale for the assessment and rating of ataxia (SARA), should be developed into a generally accepted instrument that can be used in upcoming clinical trials. Furthermore, there is an urgent need (i) to obtain more data on ataxia-specific, patient-reported outcome measures (PROs), (ii) to demonstrate and optimize sensitivity to change of many COAs, and (iii) to establish methods and evidence of anchoring change in COAs in patient meaningfulness, e.g., by determining patient-derived minimally meaningful thresholds of change.

Applying landscape metrics to species distribution model predictions to characterize internal range structure and associated changes - Amelia Curd; Mathieu Chevalier; Mickaël Vasquez; Aurélien Boyé; Louise B. Firth; Martin P. Marzloff; Lucy M. Bricheno; Michael T. Burrows; Laura E. Bush; Céline Cordier; Andrew J. Davies; J. A. Mattias Green; et al. (Global Change Biology, 2023)
Distributional shifts in species ranges provide critical evidence of ecological responses to climate change. Assessments of climate‐driven changes typically focus on broad‐scale range shifts (e.g. poleward or upward), with ecological consequences at regional and local scales commonly overlooked. While these changes are informative for species presenting continuous geographic ranges, many species have discontinuous distributions—both natural (e.g. mountain or coastal species) or human‐induced (e.g. species inhabiting fragmented landscapes)—where within‐range changes can be significant. Here, we use an ecosystem engineer species ( Sabellaria alveolata ) with a naturally fragmented distribution as a case study to assess climate‐driven changes in within‐range occupancy across its entire global distribution. To this end, we applied landscape ecology metrics to outputs from species distribution modelling (SDM) in a novel unified framework. SDM predicted a 27.5% overall increase in the area of potentially suitable habitat under RCP 4.5 by 2050, which taken in isolation would have led to the classification of the species as a climate change winner. SDM further revealed that the latitudinal range is predicted to shrink because of decreased habitat suitability in the equatorward part of the range, not compensated by a poleward expansion. The use of landscape ecology metrics provided additional insights by identifying regions that are predicted to become increasingly fragmented in the future, potentially increasing extirpation risk by jeopardising metapopulation dynamics. This increased range fragmentation could have dramatic consequences for ecosystem structure and functioning. Importantly, the proposed framework—which brings together SDM and landscape metrics—can be widely used to study currently overlooked climate‐driven changes in species internal range structure, without requiring detailed empirical knowledge of the modelled species. This approach represents an important advancement beyond predictive envelope approaches and could reveal itself as paramount for managers whose spatial scale of action usually ranges from local to regional.

Thermal integration of waste to energy plants with Post-combustion CO2 capture - Dan Su; Laura Herraiz; Mathieu Lucquiaud; Camilla Thomson; Hannah Chalmers (Fuel, 2023)

Otolith chemical composition suggests local populations of Antarctic silverfish Pleuragramma antarctica (Boulenger, 1902) around Antarctica are exposed to similar environmental conditions at early life stages - Antonio Di Franco; Antonio Calò; Giuseppe Egidio De Benedetto; Laura Ghigliotti; Antonio Pennetta; Mathieu D. M. Renard; Eva Pisano; Marino Vacchi; Paolo Guidetti (Polar Biology, 2021)

European beech stem diameter grows better in mixed than in mono-specific stands at the edge of its distribution in mountain forests - Hans Pretzsch; Torben Hilmers; Enno Uhl; Kamil Bielak; Michal Bosela; Miren del Rio; Laura Dobor; David I. Forrester; Thomas A. Nagel; Maciej Pach; Admir Avdagić; Michal Bellan; et al. (European Journal of Forest Research, 2021)
Recent studies show that several tree species are spreading to higher latitudes and elevations due to climate change. European beech, presently dominating from the colline to the subalpine vegetation belt, is already present in upper montane subalpine forests and has a high potential to further advance to higher elevations in European mountain forests, where the temperature is predicted to further increase in the near future. Although essential for adaptive silviculture, it remains unknown whether the upward shift of beech could be assisted when it is mixed with Norway spruce or silver fir compared with mono-specific stands, as the species interactions under such conditions are hardly known. In this study, we posed the general hypotheses that the growth depending on age of European beech in mountain forests was similar in mono-specific and mixed-species stands and remained stable over time and space in the last two centuries. The scrutiny of these hypotheses was based on increment coring of 1240 dominant beech trees in 45 plots in mono-specific stands of beech and in 46 mixed mountain forests. We found that (i) on average, mean tree diameter increased linearly with age. The age trend was linear in both forest types, but the slope of the age–growth relationship was higher in mono-specific than in mixed mountain forests. (ii) Beech growth in mono-specific stands was stronger reduced with increasing elevation than that in mixed-species stands. (iii) Beech growth in mono-specific stands was on average higher than beech growth in mixed stands. However, at elevations > 1200 m, growth of beech in mixed stands was higher than that in mono-specific stands. Differences in the growth patterns among elevation zones are less pronounced now than in the past, in both mono-specific and mixed stands. As the higher and longer persisting growth rates extend the flexibility of suitable ages or size for tree harvest and removal, the longer-lasting growth may be of special relevance for multi-aged silviculture concepts. On top of their function for structure and habitat improvement, the remaining old trees may grow more in mass and value than assumed so far.

Broad‐front migration leads to strong migratory connectivity in the lesser kestrel ( Falco naumanni ) - Maurizio Sarà; Salvatore Bondì; Ana Bermejo; Mathieu Bourgeois; Mathias Bouzin; Javier Bustamante; Javier de la Puente; Angelos Evangelidis; Annagrazia Frassanito; Egidio Fulco; Giuseppe Giglio; Gradimir Gradev; et al. (Journal of Biogeography, 2019)
Aim Migratory animals regularly move between often distant breeding and non‐breeding ranges. Knowledge about how these ranges are linked by movements of individuals from different populations is crucial for unravelling temporal variability in population spatial structuring and for identifying environmental drivers of population dynamics acting at different spatio‐temporal scales. We performed a large‐scale individual‐based migration tracking study of an Afro‐Palaearctic migratory raptor, to determine the patterns of migratory connectivity of European breeding populations. Location Europe, Africa. Methods Migration data were recorded using different devices (geolocators, satellite transmitters, Global Positioning System dataloggers) from 87 individuals breeding in the three core European populations, located in the Iberian, Italian and Balkan peninsulas. We estimated connectivity by the Mantel correlation coefficient ( r M ), and computed both the degree of separation between the non‐breeding areas of individuals from the same population (i.e. the population spread) and the relative size of the non‐breeding range (i.e. the non‐breeding range spread). Results European lesser kestrels migrated on a broad front across the Mediterranean Sea and Sahara Desert, with different populations using different routes. Iberian birds migrated to western Sahel (Senegal, Mauritania, western Mali), Balkan birds migrated chiefly to central‐eastern Sahel (Niger, Nigeria, Chad), whereas Italian ones spread from eastern Mali to Nigeria. Spatial differentiation of non‐breeding areas led to a strong migratory connectivity ( r M = .58), associated with a relatively high population (637 km) and non‐breeding range (1,149 km) spread. Main conclusions Our comprehensive analysis of the non‐breeding distribution of European lesser kestrel populations revealed a strong migratory connectivity, a rare occurrence in long‐distance avian migrants. The geographical conformation of the species’ breeding and non‐breeding ranges, together with broad‐front migration across ecological barriers, promoted the differentiation of migratory routes and non‐breeding areas. Strong connectivity could then arise because of both high population spread and broad non‐breeding range.

A Global Ocean Observing System (GOOS), Delivered Through Enhanced Collaboration Across Regions, Communities, and New Technologies - Tim Moltmann; Jon Turton; Huai-Min Zhang; Glenn Nolan; Carl Gouldman; Laura Griesbauer; Zdenka Willis; Ángel Muñiz Piniella; Sue Barrell; Erik Andersson; Champika Gallage; Etienne Charpentier; et al. (Frontiers in Marine Science, 2019)

Ghrelin Causes a Decline in GABA Release by Reducing Fatty Acid Oxidation in Cortex - Joan Francesc Mir; Sebastián Zagmutt; Mathieu P Lichtenstein; Judit García-Villoria; Minéia Weber; Ana Gracia; Gemma Fabriàs; Josefina Casas; Miguel López; Núria Casals; Antònia Ribes; Cristina Suñol; et al. (Molecular Neurobiology, 2018)

Characterization of a hotspot for mimicry: assembly of a butterfly wing transcriptome to genomic sequence at the HmYb/Sb locus - LAURA FERGUSON; SIU FAI LEE; NICOLA CHAMBERLAIN; NICOLA NADEAU; MATHIEU JORON; SIMON BAXTER; PAUL WILKINSON; ALEXIE PAPANICOLAOU; SUJAI KUMAR; THUAN‐JIN KEE; RICHARD CLARK; CLAIRE DAVIDSON; et al. (Molecular Ecology, 2010)
The mimetic wing patterns of Heliconius butterflies are an excellent example of both adaptive radiation and convergent evolution. Alleles at the HmYb and HmSb loci control the presence/absence of hindwing bar and hindwing margin phenotypes respectively between divergent races of Heliconius melpomene , and also between sister species. Here, we used fine‐scale linkage mapping to identify and sequence a BAC tilepath across the HmYb/Sb loci. We also generated transcriptome sequence data for two wing pattern forms of H. melpomene that differed in HmYb/Sb alleles using 454 sequencing technology. Custom scripts were used to process the sequence traces and generate transcriptome assemblies. Genomic sequence for the HmYb/Sb candidate region was annotated both using the MAKER pipeline and manually using transcriptome sequence reads. In total, 28 genes were identified in the HmYb/Sb candidate region, six of which have alternative splice forms. None of these are orthologues of genes previously identified as being expressed in butterfly wing pattern development, implying previously undescribed molecular mechanisms of pattern determination on Heliconius wings. The use of next‐generation sequencing has therefore facilitated DNA annotation of a poorly characterized genome, and generated hypotheses regarding the identity of wing pattern at the HmYb/Sb loci.